The origins of political order from prehuman times to the French Revolution - Fukuyama, Francis (Profile Books, 2012)
This book examines the paths that different societies have taken to reach their current forms of political order. It starts with the very beginning of mankind and comes right up to the eve of the French and American revolutions.